Infant Feeding and the Incidence of Endometrial Cancer - Xue, Fei (2008)
Biological mechanisms could support both an inverse and a direct association between exposure to breast milk in infancy and the risk of cancer. Having been breast-fed has been investigated in relation to the risk of breast and other cancer sites, and conflicting results have been reported. The association between infant feeding and the risk of endometrial cancer has not been explored. From 1976 to 2004, we followed 74,757 cancer-free participants in the Nurses’ Health Study who had not undergone hysterectomy. Information on infant feeding was self-reported by study participants. A total of 708 incident cases of endometrial cancer were diagnosed during follow-up. After adjusting for age, family history of endometrial cancer, birth weight, premature birth, and birth order, the incidence of endometrial cancer was not associated with ever having been breast-fed (hazards ratio, 0.94; 95% confidence interval, 0.79–1.11) or duration of having been breast-fed [hazards ratio (95% confidence interval): 1.11 (0.80–1.54), 0.84 (0.62–1.13), 1.02 (0.79–1.31), respectively, for ≤3, 4–8, and ≥9 months of having been breastfed; P for trend = 0.88]. There was no significant effect modification by menopausal status, anthropometric factors (somatotype at age 5 or 10 years, body mass index at age 18 years, or current body mass index), or by other early-life exposures (birth weight, premature birth or exposure to parental smoking in childhood). Additional adjustment for adulthood risk factors of endometrial cancer did not materially change the results. Having been breast-fed was not associated with the incidence of endometrial cancer in this cohort, but statistical power for analyses restricted to premenopausal women was limited.